(5x+30)+(11x-6)+(6x+24)=180

Simple and best practice solution for (5x+30)+(11x-6)+(6x+24)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+30)+(11x-6)+(6x+24)=180 equation:



(5x+30)+(11x-6)+(6x+24)=180
We move all terms to the left:
(5x+30)+(11x-6)+(6x+24)-(180)=0
We get rid of parentheses
5x+11x+6x+30-6+24-180=0
We add all the numbers together, and all the variables
22x-132=0
We move all terms containing x to the left, all other terms to the right
22x=132
x=132/22
x=6

See similar equations:

| (x+8)^2=49 | | 12x+9-3=12x+6 | | 5m=-515 | | 3p-5(p-1)=-13 | | −5x+2x−27=33 | | k6+9=25 | | 21=6^3x | | 17=z/19 | | 5x2-10x-6=0 | | 46=7r | | -4x+25=+7 | | F(x)=3x2x+3 | | v/(-9)=12 | | 2x+25x-25=2 | | 6(t+6)=24 | | -7(6+f)=49 | | -4a-16a-(-6)+-8=6 | | 4-(x+5)=-11 | | X+0.2x=4000 | | (x)/(4)-6=-19 | | 17=5k=2 | | x+52=62 | | 1=-4n+7+2n | | 8x-3=3(x-6) | | 66=-9n+16n-4 | | 5y–7=25–7= | | z-(-16)=53 | | 5y–7=25–7 | | 3m=-216 | | 3x+25x+20=-8 | | s-(-20)=19 | | 11^5x=6^-x+2 |

Equations solver categories